2020
DOI: 10.3389/fnsyn.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rac GTPase in Dendritic Spine Morphogenesis and Memory

Abstract: The ability to form memories in the brain is needed for daily functions, and its impairment is associated with human mental disorders. Evidence indicates that long-term memory (LTM)-related processes such as its consolidation, extinction and forgetting involve changes of synaptic efficacy produced by alterations in neural transmission and morphology. Modulation of the morphology and number of dendritic spines has been proposed to contribute to changes in neuronal transmission mediating such LTM-related process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 138 publications
3
37
0
Order By: Relevance
“…Recent studies in animal models have shown that spine alterations in the prefrontal cortex of male HIV-transgenic rats involve an actin depolymerization pathway regulated by the small GTPase Ras-related C3 botulinum toxin substrate 1 (Rac1) [ 84 ]. Normally, Rac1 activation leads to phosphorylation and activation of p21-activated kinase 1 (PAK1), which phosphorylates LIM kinase 1 (LIMK1), an inhibitor of the actin severing protein cofilin [ 162 , 163 ]. However, activation of Rac1 and PAK1 is reduced in frontal cortex of HIV-transgenic rats [ 84 ], suggesting an increase of cofilin-mediated actin severing that could drive loss of dendritic spines in this region.…”
Section: Mechanisms That Affect Synaptodendritic Damage and Network Dysfunction In Handmentioning
confidence: 99%
“…Recent studies in animal models have shown that spine alterations in the prefrontal cortex of male HIV-transgenic rats involve an actin depolymerization pathway regulated by the small GTPase Ras-related C3 botulinum toxin substrate 1 (Rac1) [ 84 ]. Normally, Rac1 activation leads to phosphorylation and activation of p21-activated kinase 1 (PAK1), which phosphorylates LIM kinase 1 (LIMK1), an inhibitor of the actin severing protein cofilin [ 162 , 163 ]. However, activation of Rac1 and PAK1 is reduced in frontal cortex of HIV-transgenic rats [ 84 ], suggesting an increase of cofilin-mediated actin severing that could drive loss of dendritic spines in this region.…”
Section: Mechanisms That Affect Synaptodendritic Damage and Network Dysfunction In Handmentioning
confidence: 99%
“…srGAP3 interacts with a scaffold protein for actin remodeling, WAVE-1, and inhibits Rac1 activity ( Soderling et al, 2002 ). Because either the inhibition of or activation of Rac1 leads to abnormal spine formation ( Costa et al, 2020 ), precise regulation of Rac1 activity is crucial for normal spine formation. Consistent with this notion, both a reduced interaction between srGAP3 and WAVE-1 and knockout of srGAP3 have been shown to decrease the number of spines ( Soderling et al, 2007 ; Carlson et al, 2011 ).…”
Section: Srgap and Robo Signaling In Spine Formationmentioning
confidence: 99%
“…Hayashi-Takagi et al ( 2015 ) developed a revolutionary approach that finally allowed tackling this question. They developed a photoactivatable form of the Rho GTPase RAC1, known to regulate spine dynamics through the modulation of actin polymerization (Costa et al, 2020 ), which they called paRAC1. RAC1 normally accumulates in recently formed, nascent spines, and constitutive RAC1 activation leads to spine shrinkage and elimination (Tashiro et al, 2000 ).…”
Section: The Causative Role Of Spine Dynamics In Learning and Behaviomentioning
confidence: 99%
“…Also, recent genetic studies have shown that many mutations associated with neurodevelopmental disorders involve genes encoding regulators of the spine actin cytoskeleton (Borovac et al, 2018 ), validating the hypothesis that mechanisms regulating the actin cytoskeleton may contribute to spine pathology in neurodevelopmental disorders. For a more complete review of actin and ABPs in spinogenesis, please refer to Costa et al ( 2020 ) in this issue of Frontiers in Synaptic Neuroscience, and Borovac et al ( 2018 ).…”
Section: Molecular Mechanisms Of Dendritic Spine Plasticitymentioning
confidence: 99%
See 1 more Smart Citation